Biomechanics of the L5–S1 motion segment after total disc replacement – Influence of iatrogenic distraction, implant positioning and preoperative disc height on the range of motion and loading of facet joints. Issue 12 (18th September 2015) - Dreischarf, Marcel; Schmidt, Hendrik; Putzier, Michael; Zander, Thomas
Abstract Total disc replacement has been introduced to overcome negative side effects of spinal fusion. The amount of iatrogenic distraction, preoperative disc height and implant positioning have been considered important for surgical success. However, their effect on the postoperative range of motion (RoM) and loading of the facets merits further discussion. A validated osteoligamentous finite element model of the lumbosacral spine was employed and extended with four additional models to account for different disc heights. An artificial disc with a fixed center of rotation (CoR) was implemented in L5–S1. In 4000 simulations, the influence of distraction and the CoR's location on the RoM, facet joint forces (FJFs) and facet capsule ligament forces (FCLFs) was investigated. Distraction substantially altered segmental kinematics in the sagittal plane by decreasing range of flexion (0.5° per 1 mm of distraction), increasing range of extension (0.7°/mm) and slightly affecting complete sagittal RoM (0.2°/mm). The distraction already strongly increased the FCLFs during surgery (up to 230 N) and in flexion (~12 N/mm), with higher values in models with larger preoperative disc heights, and increased FJFs in extension. A more anterior implant location decreased the RoM in all planes. In most loading cases, a more posterior location of the implant's CoR increased the FJFs and FCLFs, whereas a more caudal location increased the FCLFs but decreased the FJFs. The results of this study may explain the worse clinical results in patients with overdistraction after TDR. The complete RoM in the sagittal plane appears to be insensitive to detecting surgery-related biomechanical changes.